2024
DOI: 10.3390/jcm13061824
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Risk Factors Predicting Cataract Surgery Complications in Patients with Pseudoexfoliation Syndrome: A Systematic Review

Laura Denisa Preoteasa,
George Baltă,
Florian N. Baltă

Abstract: (1) Background: The present review aims to identify risk factors with predictive value for differentiating between pseudoexfoliation patients at risk of developing intra- or postoperative complications and those without operative risk during cataract surgery. (2) Methods: The review protocol was registered at PROSPERO, registration no. CRD42023417721. The following databases were searched for studies between 2000 and 2023: PubMed/Medline, Scopus, Springer, Science Direct, Web of Science, Cochrane Database of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Preoteasa et al reported 156 perioperative incidents in 999 eyes with pseudoexfoliation, with predictive factors identified as a shallow anterior chamber, cataract grade, preoperative intraocular pressure, and symmetry of the exfoliation material [ 36 ]. Similar reports were also mentioned by Vazquez-Ferreiro et al [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoteasa et al reported 156 perioperative incidents in 999 eyes with pseudoexfoliation, with predictive factors identified as a shallow anterior chamber, cataract grade, preoperative intraocular pressure, and symmetry of the exfoliation material [ 36 ]. Similar reports were also mentioned by Vazquez-Ferreiro et al [ 37 ].…”
Section: Discussionmentioning
confidence: 99%